2007
DOI: 10.1186/1477-9560-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mechanical thrombectomy for the treatment of acute massive pulmonary embolism: case report

Abstract: Background: To our knowledge we report the first case of percutaneous mechanical thrombectomy used for the treatment of massive pulmonary embolism in the United Kingdom. Pulmonary embolism is a common disease process but can be difficult to diagnose. Massive pulmonary embolism presenting with profound hypotension, however, is rare. Both phenomena carry with them significant mortality. Traditionally those patients suffering haemodynamic compromise from pulmonary embolism are treated with intravenous or catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…5,18 In this case, given the high percentage of poor outcomes for mechanical thrombectomy due to peripheral embolisms and the severity of our patient, it was decided to add thrombolysis with intermediate doses of urokinase for mechanical thrombectomy. 4,8,13,15,16 Our patient's outcome was good and she had no hemorrhagic complications. To our knowledge, this is the first reported case with concomitant mechanical thrombectomy, arterial thrombolysis and inferior vena cava filter placement.…”
Section: Discussionmentioning
confidence: 82%
“…5,18 In this case, given the high percentage of poor outcomes for mechanical thrombectomy due to peripheral embolisms and the severity of our patient, it was decided to add thrombolysis with intermediate doses of urokinase for mechanical thrombectomy. 4,8,13,15,16 Our patient's outcome was good and she had no hemorrhagic complications. To our knowledge, this is the first reported case with concomitant mechanical thrombectomy, arterial thrombolysis and inferior vena cava filter placement.…”
Section: Discussionmentioning
confidence: 82%
“…However, the major complications of PT include renal failure, bradycardia, stroke, and death; they constitute less than 5.0% of overall cases. 10,11 There are two types of mechanism of thrombus removal, which can be broadly divided into mechanical thrombectomy and suction thrombectomy. 5 Mechanical thrombectomy involves breaking the clot before removing it, which can be done via a simple procedure such as rotating the catheter within the thrombus, using an angioplasty balloon, or using more sophisticated devices as is the case in rheolytic thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Morbidity with Other Case Series of PMT Morbidity in the present study is lower than what has been reported in prior case series. A review of the literature published to date using the Angiojet system for PMT of massive PE reveals 83 patients 11–15,17–30 . In 22% of those patients (18 of 83) some form of bleeding complication was reported such as bleeding–not further specified, hemoptysis, or the need for transfusion (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature published to date using the Angiojet system for PMT of massive PE reveals 83 patients. [11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In 22% of those patients (18 of 83) some form of bleeding complication was reported such as bleeding-not further specified, hemoptysis, or the need for transfusion ( Table 3). Several of those reported bleeding episodes may be due to vascular access and not necessarily related to the PMT procedure.…”
Section: Discussionmentioning
confidence: 99%